The Role of Character-Building Programs in Forming Students' Social Character in Islamic Education Management - Kusumawati, Hesti; Bani Amien , Nelya (IAIN Madura, 2025)
Although Islamic values ​​teach the importance of good morals and social behavior, the implementation of these values ​​in students' daily lives is often hampered by differences in social, cultural, and economic backgrounds that students have. This study aims to analyze how the character-building program at the Institution contributes to the formation of students' social character in Islamic Education management. This study uses a descriptive qualitative approach. The location of this study is Puncak Darussalam Islamic Boarding School located in Potoan Daja Village, Palengaan District, Pamekasan Regency. The findings can be concluded that the Character-Building program in Islamic education management has an important role in forming students' social character so that they become individuals with noble morals, increase social awareness and concern for others, and are responsible so that they are able to interact well in their social environment.